Elevated childhood separation anxiety: An early developmental expression of heightened concern for kin in homosexual men?. (July 2015) - VanderLaan, Doug P.; Petterson, Lanna J.; Vasey, Paul L.
Highlights: Concern about kin may be a childhood expression of kin-directed altruism in gay men. Femininity is linked to recalled separation anxiety in heterosexual females and homosexual males. Gay male femininity may facilitate kin-directed altruism development. Abstract: This study presents data bearing on an evolutionary developmental model of male homosexuality. This model hypothesizes that a predisposition toward elevated kin-directed altruism among homosexual males is expressed in childhood as elevated concern for close attachment figures (e.g., parents) and proximally influenced by the concomitant behavioral expression of femininity. We examined whether homosexual males recalled such elevated concern for parents during childhood and considered its association with recalled childhood gender behavior. Heterosexual and homosexual males and females ( N  = 524) provided measures of recalled childhood gender behavior, concern about parental wellbeing, and other potential sources of separation anxiety. Heterosexual males experienced significantly less anxiety about parental wellbeing than all other groups. Recalled separation anxiety was positively correlated with childhood femininity for heterosexual females and homosexual males. The heterosexual sex and male sexual orientation differences in concern about parental wellbeing were accounted for by childhood feminine behavior. These findings are consistent with the proposed evolutionary developmental model. We discuss possible proximate influences that facilitate the development of this putative evolved predisposition toward elevated kin-directed altruism among homosexual males as well as limitations and future directions.